Smart Cane: A Safety and Mobility Enhancement Tool for the Elderly and Visually Impaired - Marjohan, Muhammad Idzhan; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2025)
The Smart Cane project introduces an advanced mobility aid designed to enhance safety and independence for the visually impaired and elderly. It features obstacle detection using an ToF sensor, LED illumination for dark areas, and an emergency alert system that sends real-time location notifications to family or close contacts. It also includes water detection to prevent slips on wet surfaces. Unlike conventional mobility aids, this device integrates assistive technology that gives haptic feedback through vibrations when obstacles are detected. The Smart Cane bridges the gap between traditional aids and the growing needs of users in today’s dynamic world.